Challenges of NTM Drug Development - Falkinham, Joseph O. (Frontiers in Microbiology, 2018)
Discovery and development of antibiotics active against the environmental opportunistic nontuberculous mycobacteria (NTM) have been retarded by innate antibiotic-resistance of NTM cells and methodological challenges in the laboratory. The basis for the innate resistance of NTM cells is its lipid rich outer membrane that results in hydrophobic cells and the outer membrane’s impermeability, and the residence of NTM cells in phagocytic cells, and the slow growth and dormancy of NTM. Laboratory challenges include: the choice of species and strains for screening and measurement of anti-NTM activity, the high frequency colony switching between antibiotic-susceptible and resistant variants, the preference of NTM to adhere to surfaces and form biofilms, and the aggregation of NTM cells. Understanding these challenges can guide and inform our approaches to discovery and development of antibiotics with activity against NTM.